In Vitro Seed Germination and Shoot Growth of Nepenthes jamban Chi. C. Lee, Hernawati & Akhriadi, A Unique Pitcher Plant from Indonesia - Prawestri, Apriliana Dyah; Rahayu, Resa Sri; Kurniajati, Wulan Septiningtyas; Sunardi, Sunardi; Mansur, Muhammad (Universitas Gadjah Mada, 2024)
The study to optimize in vitro propagation of the Indonesian native and critically endangered species, Nepenthes jamban, in order to support the ex-situ conservation efforts has been done. Using Murashige and Skoog (MS) as a basal media, disinfected seeds of N. jamban were germinated on five types of germination media, viz. ¼ MS, ½ MS, MS, ¼ MS+benzyl adenine (BA)+Biotin and MS+BA+Biotin. Afterwards, in vitro shoots with 6-7 leaves were inoculated on growing media, i.e., ¼ MS, ¼ MS 60 (3:1) (MS modification with a higher concentration of nitrogen), and ¼ MS+naphtalene acetic acid (NAA)+BA. The results showed that the germination of N. jamban seeds was slow, indicated by the percentage of germination being less than 20% after 6 months of being planted on germination media. The highest percentage of germination was after the 6th month and the greatest pitcher development at the 10th month were obtained on ¼ MS medium. Furthermore, shoot growth and pitchers development consistently increased for 12 months in ¼ MS 60 (3:1) medium while other media resulted in a decrease in pitcher formation. It seemed that low concentrations of nutrient in the medium proved to be more effective to induce in vitro seed germination and enhance shoot growth which was also supported by higher nitrogen (nitrate) concentration in the medium. This study provides information that supports ex situ conservation action of native and critically endangered Nepenthes species from Indonesia.